Connecting the Dots of Brand Experience and Happiness: The Mediating Role of Happiness Orientations - Imran Sarmad; Rizwan Ali (Reviews of Management Sciences, 2022)
Purpose: Consumer research studies that have already been conducted on happiness have claimed that businesses should make their customers happier via experiences, but they have not addressed how specific brand experience elements may make customers happier. To address this gap, the main purpose of this research is to investigate the impact of brand experience on happiness via happiness orientations.